2010
DOI: 10.4236/ns.2010.22011
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of swimming pools with chlorine and derivatives: formation of organochlorinated and organobrominated compounds and exposure of pool personnel and swimmers

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…The MCLs of the total THMs in tap water should not be higher than 80 μg/L (USEPA phase I) with the MCL goal (MCLG) for the total THM concentration at 40 μg/L (USEPA phase II) 33,34 . The mean concentration of TTHM in all herbal spa samples was higher than the mean THM levels in swimming pool water in several other studies 35–37 . The potential to generate high levels of chlorinated by-products on a daily basis in the herbal spa community could represent an environmental and health assessment problem because long-term exposure to high THM levels (>50 µg/L) could result in serious health problems, such as bladder cancer 38 .…”
Section: Resultscontrasting
confidence: 60%
“…The MCLs of the total THMs in tap water should not be higher than 80 μg/L (USEPA phase I) with the MCL goal (MCLG) for the total THM concentration at 40 μg/L (USEPA phase II) 33,34 . The mean concentration of TTHM in all herbal spa samples was higher than the mean THM levels in swimming pool water in several other studies 35–37 . The potential to generate high levels of chlorinated by-products on a daily basis in the herbal spa community could represent an environmental and health assessment problem because long-term exposure to high THM levels (>50 µg/L) could result in serious health problems, such as bladder cancer 38 .…”
Section: Resultscontrasting
confidence: 60%
“…In Italy, Fernández-Luna et al 169 The concentration of chloroform (CHCI 3 ) has been reported by several authors. 4,165,[173][174][175][176][177][178] For example, in Europe, the reported mean chloroform concentrations in the air of indoor swimming pools ranged between 35 µg/m 3 and 55 µg/m 3 . 4,165,179 It should be noted that the presence of chloroform indicates the formation and potential for exposure to additional chlorine disinfection by-products, such as chloramines (CAMs).…”
Section: Indoor Swimming Poolsmentioning
confidence: 99%
“…THMs are a volatile class of DBP and, as such, can partition from the water into the ambient air of swimming pool complexes, where concentrations have been shown to increase with water agitation either by swimmers or by water jets . Many studies have reported the occurrence of THMs in the air above swimming pool and spa waters, and THMs have also been reported in passageways, offices/reception areas, café areas, plant/engine rooms, and change rooms in pool complexes …”
Section: Introductionmentioning
confidence: 99%
“…Inhalation has been shown to be the major route of exposure for THMs in the swimming pool environment . Higher exposure to THMs was reported for employees who worked pool side compared to those working in reception or plant room areas of the same facility .…”
Section: Introductionmentioning
confidence: 99%